A high-boron protective glaze suitable for rapid firing of a roller kiln and a method for preparing architectural ceramic using the high-boron protective glaze

CN122977702APending Publication Date: 2026-10-27MONALISA GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611425942.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]针对现有快烧釉料体系中硼含量提升受限、易出现釉面鼓包与氧化缺陷的问题,本发明以硼酸锌与自制高硼熔块为核心功能组分,开发出一种适用于辊道窑快速烧成的高硼保护釉及使用该高硼保护釉的建筑陶瓷制备方法

Benefits of technology

针对现有快烧釉料体系中硼含量提升受限、易出现釉面鼓包与氧化缺陷的问题,本发明以硼酸锌与自制高硼熔块为核心功能组分,开发出一种适用于辊道窑快速烧成的高硼保护釉及使用该高硼保护釉的建筑陶瓷制备方法,从根本上避免快烧制度下高硼保护釉易出现的氧化不良、釉面鼓包、针孔与暗斑等缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977702A_ABST
    Figure CN122977702A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of building ceramic production and manufacturing, and particularly relates to a high-boron protective glaze suitable for rapid firing of a roller kiln and a building ceramic preparation method using the high-boron protective glaze. Mineral composition of the high-boron protective glaze includes, in terms of mass percentage, quartz 5-20%, kaolin 5-10%, calcined talc 2-8%, wollastonite 10-20%, albite 20-50%, high-boron frit 5-20%, and zinc borate 5-20%. In view of the problems that the boron content in the existing fast-firing glaze system is limited and is prone to glaze bulging and oxidation defects, the present application takes zinc borate and self-made high-boron frit as core functional components, and develops a high-boron protective glaze suitable for rapid firing of a roller kiln and a building ceramic preparation method using the high-boron protective glaze.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building ceramics production and manufacturing technology, specifically to a high-boron protective glaze suitable for rapid firing in a roller kiln and a method for preparing building ceramics using the high-boron protective glaze. Background Technology

[0002] Low-temperature rapid firing technology is one of the core technological pathways for reducing energy consumption in the building ceramics industry. This technology optimizes the body and glaze formulation system and firing regime, significantly reducing firing temperature and shortening the firing cycle, thus achieving a substantial decrease in energy consumption per unit product. Industry general trends show that for every 100°C reduction in firing temperature, fuel consumption can be saved by approximately 10% to 15%, and the rapid firing process can effectively improve kiln capacity utilization. Therefore, low-temperature rapid firing possesses the dual value of energy conservation and emission reduction, as well as improved quality and efficiency, making it a key breakthrough for the building ceramics industry to achieve green and low-carbon development.

[0003] Boron oxide (B2O3) possesses unique glass network regulating properties and excellent low-temperature fluxing performance, making it one of the most widely used core fluxing components in low-temperature glaze systems. B2O3 can participate in the depolymerization and recombination of the silicon-oxygen network at relatively low temperatures, significantly reducing the high-temperature viscosity of the glaze and promoting the formation of a smooth and dense glassy coating on the glaze surface within a short firing cycle. It is an indispensable key component in low-temperature fast-firing glaze formulations.

[0004] However, under rapid firing conditions, boron-containing glazes melt quickly and form a dense, glassy covering layer, sealing off the organic matter and carbon within the ceramic body before they are fully oxidized and decomposed. The residual carbon continues to oxidize and generate gas after being sealed on the glaze surface, causing glaze blistering defects. The insufficiently oxidized organic matter and carbon also lead to localized color differences and dark spots on the glaze surface. These defects worsen with increasing boron content in the glaze. Therefore, the boron oxide content in current conventional architectural ceramic glaze systems is generally below 5 wt%, making it difficult to further reduce the firing temperature by increasing the boron content. Summary of the Invention

[0005] To address the limitations in increasing boron content and the tendency for glaze blistering and oxidation defects in existing fast-firing glaze systems, this invention develops a high-boron protective glaze suitable for rapid firing in roller kilns, using zinc borate and a self-made high-boron frit as core functional components, and a method for preparing architectural ceramics using this high-boron protective glaze. This invention is achieved through the following technical solutions: On one hand, the present invention provides a high-boron protective glaze suitable for rapid firing in roller kilns. The mineral composition of the high-boron protective glaze includes, by mass percentage: 5%–20% quartz, 5%–10% kaolin, 2%–8% calcined talc, 10%–20% wollastonite, 20%–50% albite, 5%–20% high-boron frit, and 5%–20% zinc borate.

[0006] In an optional embodiment, the mineral composition of the high-boron frit includes, by mass percentage: 36%–40% quartz, 30%–35% borax, 18%–25% soda ash (sodium carbonate), and 10%–13% calcite.

[0007] In an optional embodiment, the chemical composition of the high-boron ingot includes, by mass percentage: SiO2: 38%–50%, CaO: 7%–10%, Na2O: 18%–25%, B2O3: 25%–35%.

[0008] In an optional embodiment, the chemical composition of the high-boron protective glaze includes, by mass percentage: SiO2: 50%–60%, Al2O3: 8%–12%, Fe2O3: 0.1%–0.3%, TiO2: 0.03%–0.35%, CaO: 1%–8%, MgO: 1%–2%, K2O: 0.2%–0.5%, Na2O: 5%–9%, ​​ZnO: 1.5%–7%, B2O3: 6%–15%, and loss on ignition: 2.5%–4%.

[0009] On the other hand, the present invention provides a method for preparing building ceramics using the high boron protective glaze, comprising the following steps: applying a surface glaze to the surface of a green body; inkjet printing an ink decorative pattern on the surface of the green body after applying the surface glaze; applying the high boron protective glaze suitable for rapid firing in a roller kiln to the surface of the green body after inkjet printing the ink decorative pattern; firing and polishing the green body after applying the high boron protective glaze to obtain building ceramics.

[0010] In an optional embodiment, the high-boron protective glaze is applied by spraying, and the glaze specific gravity is controlled to be 1.4–1.6 g / cm³. 3 The glaze application rate is 600–800 g / m². 2 .

[0011] In an optional embodiment, the chemical composition of the glaze includes, by mass percentage: SiO2: 50%–60%, Al2O3: 20%–30%, Fe2O3: 0.1%–0.3%, TiO2: 0.01%–0.15%, CaO: 0.2%–1.6%, MgO: 0.1%–0.5%, K2O: 4%–5%, Na2O: 2%–3%, P2O5: 0.01%–0.1%, ZrO2: 4%–12%, and loss on ignition: 1%–3%.

[0012] In an optional embodiment, the glaze is applied by spraying, and the glaze specific gravity is controlled to be 1.35–1.6 g / cm³. 3 The glaze application rate is 500–800 g / m². 2 .

[0013] In an optional embodiment, the firing temperature is 1170℃~1200℃ and the firing cycle is 30~40 minutes.

[0014] In an optional embodiment, the gloss of the glaze of the building ceramic after firing before polishing is 70 to 99 degrees.

[0015] Compared with the prior art, the present invention has the following beneficial effects: To address the limitations in increasing boron content and the tendency for glaze blistering and oxidation defects in existing fast-firing glaze systems, this invention develops a high-boron protective glaze suitable for rapid firing in roller kilns, using zinc borate and self-made high-boron frit as core functional components. It also provides a method for preparing architectural ceramics using this high-boron protective glaze, fundamentally avoiding defects such as poor oxidation, glaze blistering, pinholes, and dark spots that are prone to occur in high-boron protective glazes under fast-firing conditions. Attached Figure Description

[0016] Figure 1 This is a glaze effect diagram of Example 1; Figure 2 This is a glaze effect diagram of Example 2; Figure 3 This is a comparison image of the glaze effect in Example 1; Figure 4 This is a comparison image of the glaze effect in Example 2; Figure 5 This is a comparison image of the glaze effect in scale 3; Figure 6 This is a comparison image of the glaze effect (sample 4). Figure 7 This is a rendering of the blank from Comparative Example 4; Figure 8 This is a comparison image of the glaze effect (scale 5). Figure 9 This is a glaze effect diagram of Example 3; Figure 10 This is a rendering of the blank from Example 3. Detailed Implementation

[0017] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention. The following exemplary description illustrates the preparation method of high boron protective glaze and building ceramics suitable for rapid firing in roller kilns according to the present invention.

[0018] The formulation of the high boron protective glaze. The mineral composition of the high boron protective glaze of the present invention includes, by mass percentage: 5%–20% quartz, 5%–10% kaolin, 2%–8% calcined talc, 10%–20% wollastonite, 20%–50% albite, 5%–20% high boron frit, and 5%–20% zinc borate.

[0019] Zinc borate (2ZnO·3B2O3·3.5H2O) is a commonly used inorganic combustion improver with a melting point of approximately 980℃. It is currently widely used in flame-retardant systems in industries such as plastics, rubber, coatings, and textiles. This invention utilizes the thermal decomposition characteristics of zinc borate to synergistically solve the venting problem of high-boron protective glazes under rapid firing conditions through a triple mechanism: (1) Shrinkage and gap formation to expand the exhaust network: In the temperature range of 300℃~600℃, zinc borate undergoes a phased and progressive dehydration reaction. The crystal structure shrinks in volume along with the dehydration, forming micron-level gaps between the zinc borate particles and the surrounding glaze matrix, thus constructing an additional exhaust channel network inside the glaze layer.

[0020] (2) Steam purging to maintain unobstructed passage: The trace amount of water vapor continuously released during the dehydration process diffuses outward along the gap between the particles, which can prevent the exhaust passage from being blocked during the initial melting of the glaze and ensure that the exhaust path of the gas generated by the decomposition of the green body is smooth.

[0021] (3) Skeleton-based melt resistance, delaying glaze sealing: In the temperature range of 600℃ to 980℃, the high-boron frit has begun to form a liquid phase, but the anhydrous zinc borate (2ZnO·3B2O3) generated by the dehydration of zinc borate is still dispersed in the glaze liquid in the form of solid particles. Its unmelted particle skeleton can prevent the liquid phase from being completely connected, delaying the sudden sealing of the glaze surface, and leaving a time window for the full oxidation of organic matter and carbon in the body. When the temperature rises above 980℃, the anhydrous zinc borate (2ZnO·3B2O3) melts and is incorporated into the glaze liquid. The ZnO and B2O3 components in it act as fluxes to further promote the rapid densification of the glaze surface, and finally form a smooth and transparent glassy coating layer.

[0022] Through the synergistic effect of the above three mechanisms, the organic matter and carbon in the body can be fully oxidized and decomposed before the glaze is completely sealed, thus fundamentally avoiding defects such as poor body oxidation, glaze blistering, pinholes and dark spots that are prone to occur in high boron protective glaze under the fast firing process.

[0023] Formulation and preparation of high-boron frit. The mineral composition of the high-boron frit includes, by mass percentage: 36%–40% quartz, 30%–35% (pentahydrate) borax, 18%–25% soda ash, and 10%–13% calcite. The raw materials for the high-boron frit are weighed according to the above mineral formula, mixed evenly, and then melted at 1180℃–1250℃ for 2–3 hours to obtain a homogeneous glass melt. The glass melt is then rapidly water-quenched and crushed to obtain the high-boron frit. The mesh size of the high-boron frit can be 20–60 mesh.

[0024] The chemical composition of the high-boron ingot includes, by mass percentage: SiO2: 38%–50%, CaO: 7%–10%, Na2O: 18%–25%, B2O3: 25%–35%.

[0025] In an optional embodiment, the chemical composition of the high-boron protective glaze includes, by mass percentage: SiO2: 50%–60%, Al2O3: 8%–12%, Fe2O3: 0.1%–0.3%, TiO2: 0.03%–0.35%, CaO: 1%–8%, MgO: 1%–2%, K2O: 0.2%–0.5%, Na2O: 5%–9%, ​​ZnO: 1.5%–7%, B2O3: 6%–15%, and loss on ignition: 2.5%–4%.

[0026] The following is an example illustrating a method for preparing building ceramics. Building ceramics include, but are not limited to, ceramic bricks or slabs.

[0027] Preparation of green body powder. The green body powder used is a conventional green body raw material. For example, the chemical composition of the green body includes, by mass percentage: SiO2: 65%–70%, Al2O3: 17%–19%, Fe2O3: 0.1%–2%, TiO2: 0.1%–0.3%, CaO: 2.5%–5%, MgO: 0.5%–1%, K2O: 2.5%–4%, Na2O: 1.5%–3%, and loss on ignition: 4%–6%. It should be understood that any mineral composition formulation that meets the above chemical composition of the green body powder is applicable to this invention. The mineral raw materials are weighed according to the formulation and subjected to ball milling, spray granulation, aging, etc., to prepare the green body powder.

[0028] Compression molding. This involves compressing the raw material powder into shape using conventional production processes. This includes, but is not limited to, dry pressing.

[0029] Drying. The material is placed in a drying kiln for drying. For example, after pressing ceramic body powder into shape, it is dried until the moisture content is ≤0.5wt%. The drying temperature can be 180~220℃, and the drying time can be 40~60 minutes.

[0030] A surface glaze is applied to the dried body. The surface glaze can be a conventional zirconium white glaze. For example, the chemical composition of the surface glaze includes, by mass percentage: SiO2: 50%–60%, Al2O3: 20%–30%, Fe2O3: 0.1%–0.3%, TiO2: 0.01%–0.15%, CaO: 0.2%–1.6%, MgO: 0.1%–0.5%, K2O: 4%–5%, Na2O: 2%–3%, P2O5: 0.01%–0.1%, ZrO2: 4%–12%, and loss on ignition: 1%–3%.

[0031] The topcoat is applied by spraying. Optionally, the specific gravity of the topcoat is 1.35~1.6 g / cm³. 3 The glaze application rate is 500~800 g / m². 2 .

[0032] Ink patterns are printed onto the surface of the glazed body using inkjet printing. Digital inkjet printers can be used for inkjet printing decoration.

[0033] A high-boron protective glaze is applied to the surface of the substrate after inkjet printing the ink pattern. Preparation of the high-boron protective glaze slurry: Accurately weigh each mineral raw material according to the mineral composition of the high-boron protective glaze, add 0.1%~0.5% (e.g., 0.2%) of sodium carboxymethyl cellulose and 0.1%~0.5% (e.g., 0.3%) of sodium tripolyphosphate, add water, ball mill, and sieve to obtain the high-boron protective glaze slurry. The mass ratio of the total mass of the high-boron protective glaze mineral raw materials to water can be 1:(0.4~0.6). For example, the mass ratio of the total mass of the high-boron protective glaze mineral raw materials to water can be 1:0.4. The residue on a 325-mesh sieve of the high-boron protective glaze slurry should be controlled within 0.7wt%. Water can be added to the slurry before applying the high-boron protective glaze to adjust to the desired specific gravity. The high-boron protective glaze is applied by spraying, and the specific gravity is controlled at 1.4~1.6 g / cm³. 3 The glaze application rate is 600–800 g / m². 2 If the amount of high-boron protective glaze applied is too low, it will easily be polished through. If the amount of high-boron protective glaze applied is too high, the transparency of the glaze surface will decrease.

[0034] Firing process. This high-boron protective glaze is suitable for rapid firing in roller kilns. The firing temperature range is 1170℃~1200℃, and the firing cycle is 30~40 minutes.

[0035] polishing.

[0036] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0037] Example 1

[0038] The method for preparing architectural ceramics includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0039] Step 2: Apply a conventional architectural ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0040] Step 3: Print inkjet decorative patterns on the surface of the blank after applying the glaze.

[0041] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 10%, albite 40%, high-boron frit 15%, and zinc borate 10%. The mineral composition of the high-boron frit includes, by mass percentage: quartz 37.3%, (pentahydrate) borax 31.4%, soda ash 19.7%, and calcite 11.6%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2: 43%, CaO: 7.5%, Na2O: 21%, and B2O3: 28.5%. The chemical composition of the high boron protective glaze includes, by mass percentage: SiO2: 58.56%, Al2O3: 10.03%, Fe2O3: 0.13%, TiO2: 0.2%, CaO: 6.02%, MgO: 1.81%, K2O: 0.3%, Na2O: 7.13%, ZnO: 3.71%, B2O3: 9.1%, and loss on ignition: 3.01%.

[0042] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The glazing method is spray glazing, and the glaze slurry specific gravity is 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0043] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0044] Performance testing: After firing, the glaze achieved a gloss level of 71 degrees, exhibiting excellent transparency and free from defects such as bulges, pinholes, and bubbles. Figure 1 After polishing, the gloss level can reach 99 degrees.

[0045] Example 2 The building preparation method includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0046] Step 2: Apply a ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0047] Step 3: Print inkjet decorative patterns on the glazed body surface.

[0048] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 10%, albite 30%, high-boron frit 20%, and zinc borate 15%. The mineral composition of the high-boron frit includes, by mass percentage: quartz 37.3%, (pentahydrate) borax 31.4%, soda ash 19.7%, and calcite 11.6%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2: 43%, CaO: 7.5%, Na2O: 21%, and B2O3: 28.5%. The chemical composition of the high boron protective glaze includes, by mass percentage: SiO2: 53.19%, Al2O3: 8.45%, Fe2O3: 0.13%, TiO2: 0.03%, CaO: 6.38%, MgO: 1.81%, K2O: 0.36%, Na2O: 7.18%, ZnO: 5.61%, B2O3: 12.91%, and loss on ignition: 3.95%.

[0049] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The high boron protective glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0050] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0051] Performance testing: After firing, the glaze's original gloss level increased to 85 degrees, with excellent transparency and no appearance defects such as bulges, pinholes, or bubbles. Figure 2The gloss level after polishing can reach 99 degrees. Compared with Example 1, this example increases the amount of high boron frit and zinc borate, resulting in more complete glaze melting and a significant improvement in gloss, indicating that this formulation system has the potential to further reduce the firing temperature.

[0052] Comparative Example 1 The building preparation method includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0053] Step 2: Apply a ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0054] Step 3: Print inkjet decorative patterns on the glazed body surface.

[0055] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 10%, albite 50%, and high-boron frit 15%. The mineral composition of the high-boron frit includes, by mass percentage: quartz 37.3%, (pentahydrate) borax 31.4%, soda ash 19.7%, and calcite 11.6%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2: 43%, CaO: 7.5%, Na2O: 21%, and B2O3: 28.5%.

[0056] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The high boron protective glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0057] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0058] Performance testing: Under the same firing regime, obvious blistering and foaming defects appeared on the glaze surface after firing. Figure 3The reason is that, without the triple venting mechanism of zinc borate, the high-boron frit rapidly forms a continuous liquid phase at low temperatures, causing the glaze surface to close prematurely. Gases generated by the decomposition of the body cannot be smoothly released and remain inside the glaze layer, forming bubbles and bulges. This verifies the core role of zinc borate in high-boron fast-firing glazes.

[0059] Comparative Example 2 The building preparation method includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0060] Step 2: Apply a ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0061] Step 3: Print inkjet decorative patterns on the glazed body surface.

[0062] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 20%, albite 45%, and zinc borate 10%. The chemical composition of the high-boron protective glaze includes, by mass percentage: SiO2: 61.59%, Al2O3: 11.61%, Fe2O3: 0.14%, TiO2: 0.03%, CaO: 7.31%, MgO: 1.92%, K2O: 0.42%, Na2O: 4.96%, ZnO: 3.74%, B2O3: 4.81%, and loss on ignition: 3.47%.

[0063] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The high boron protective glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0064] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0065] Performance testing: Under the same firing regime, the glaze was underfired after firing, and the gloss level was only 2 degrees. Figure 4 The reason is that under the rapid firing regime, the firing time in the firing zone is short. Without the strong fluxing effect of the high boron frit, the glaze enters the cooling zone before it has melted, thus exhibiting underfiring. This verifies the core role of the high boron frit in high boron rapid firing glazes.

[0066] Comparative Example 3 The building preparation method includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0067] Step 2: Apply a ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0068] Step 3: Print inkjet decorative patterns on the glazed body surface.

[0069] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 10%, albite 25%, high-boron frit 15%, and zinc borate 25%. The mineral composition of the high-boron frit includes, by mass percentage: quartz 37.3%, (pentahydrate) borax 31.4%, soda ash 19.7%, and calcite 11.6%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2: 43%, CaO: 7.5%, Na2O: 21%, and B2O3: 28.5%. The chemical composition of the high boron protective glaze includes, by mass percentage: SiO2: 47.35%, Al2O3: 7.67%, Fe2O3: 0.14%, TiO2: 0.03%, CaO: 5.99%, MgO: 1.80%, K2O: 0.34%, Na2O: 5.63%, ZnO: 9.36%, B2O3: 16.30%, and loss on ignition: 5.39%.

[0070] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The high boron protective glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0071] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0072] Performance testing: Under the same firing regime, the glaze surface was opaque after firing, with a gloss level of 54. (See attached image) Figure 5 The reason is that after adding excessive zinc borate, the overall firing range of the glaze shifts later. Under the fast firing regime, the glaze cannot fully melt and the air bubbles in the glaze layer cannot be completely expelled before entering the cooling stage, thus exhibiting an opaque phenomenon.

[0073] Comparative Example 4 The building preparation method includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0074] Step 2: Apply a ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0075] Step 3: Print inkjet decorative patterns on the glazed body surface.

[0076] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 10%, albite 30%, high-boron frit 25%, and zinc borate 10%. The mineral composition of the high-boron frit includes, by mass percentage: quartz 37.3%, (pentahydrate) borax 31.4%, soda ash 19.7%, and calcite 11.6%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2: 43%, CaO: 7.5%, Na2O: 21%, and B2O3: 28.5%. The chemical composition of the high boron protective glaze includes, by mass percentage: SiO2: 55.33%, Al2O3: 8.45%, Fe2O3: 0.14%, TiO2: 0.03%, CaO: 6.76%, MgO: 1.80%, K2O: 0.35%, Na2O: 8.23%, ZnO: 3.74%, B2O3: 11.94%, and loss on ignition: 3.23%.

[0077] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The high boron protective glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0078] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0079] Performance testing: Under the same firing regime, the glaze bulged after firing, with a gloss level of 51, and the pattern appeared bluish. Figure 6 Poor oxidation of the billet is observed. Figure 7 The reason is that after adding an excessive amount of high-boron frit, the glaze produces a large amount of liquid phase in a short period of time, which obstructs the exhaust channel, resulting in poor oxidation of the body and blistering of the glaze surface.

[0080] Comparative Example 5 The process steps of this comparative example are basically the same as those of Example 1, the only difference being the amount of high boron protective glaze applied. The high boron protective glaze in this comparative example has an application density of 1.45 g / cm³. 3 Glazing amount 950 g / m 2 .

[0081] Performance testing: Under the same firing regime, the glaze surface was opaque after firing, with a gloss level of 69 degrees. Figure 8 This is mainly due to the increased amount of glaze applied, which leads to an increase in the number of air bubbles in the glaze layer. Under the low-temperature, high-firing conditions, the air bubbles that are not completely expelled refract and reflect light, causing the light to diffuse randomly in all directions, thus exhibiting an opaque appearance.

[0082] Example 3

[0083] The building preparation method includes the following steps: Step 1: Press the ceramic body powder into shape and then dry it.

[0084] Step 2: Apply a ceramic glaze to the surface of the dried body. The chemical composition of the glaze includes, by mass percentage: SiO2: 55.85%, Al2O3: 24.63%, Fe2O3: 0.23%, TiO2: 0.1%, CaO: 0.29%, MgO: 0.14%, K2O: 4.33%, Na2O: 2.43%, P2O5: 0.01%, ZrO2: 9.01%, and loss on ignition: 2.98%. The glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 660 g / m 2 .

[0085] Step 3: Print inkjet decorative patterns on the glazed body surface.

[0086] Step 4: Prepare the high-boron protective glaze according to the formula. The mineral raw material composition of the high-boron protective glaze includes, by mass percentage: quartz 10%, kaolin 10%, calcined talc 5%, wollastonite 20%, albite 30%, high-boron frit 15%, and zinc borate 10%. The mineral composition of the high-boron frit includes, by mass percentage: quartz 37.3%, (pentahydrate) borax 31.4%, soda ash 19.7%, and calcite 11.6%; the chemical composition of the high-boron frit includes, by mass percentage: SiO2: 43%, CaO: 7.5%, Na2O: 21%, and B2O3: 28.5%. The chemical composition of the high boron protective glaze includes, by mass percentage: SiO2: 55.74%, Al2O3: 8.49%, Fe2O3: 0.14%, TiO2: 0.03%, CaO: 10.70%, MgO: 1.99%, K2O: 0.35%, Na2O: 6.13%, ZnO: 3.74%, B2O3: 9.09%, and loss on ignition: 3.60%.

[0087] Step 5: Apply the above-mentioned high boron protective glaze to the surface of the blank with the printed inkjet pattern. The high boron protective glaze is applied by spraying, and the glaze slurry has a specific gravity of 1.45 g / cm³. 3 Glazing amount 700 g / m 2 .

[0088] Step 6: The glazed body is sent into a roller kiln for firing at a temperature of 1190℃ for 35 minutes. After firing, it is polished.

[0089] Performance testing: Under the same firing regime, the glaze exhibits excellent transparency after firing, with no appearance defects such as bulges, pinholes, or bubbles, and a gloss level of 80 degrees. Figure 9 The green body is well oxidized, see Figure 10 .

Claims

1. A high-boron protective glaze suitable for rapid firing in roller kilns, characterized in that, The mineral composition of the high boron protective glaze includes, by mass percentage: 5%–20% quartz, 5%–10% kaolin, 2%–8% calcined talc, 10%–20% wollastonite, 20%–50% albite, 5%–20% high boron frit, and 5%–20% zinc borate.

2. The high-boron protective glaze according to claim 1, characterized in that, The chemical composition of the high-boron ingot includes, by mass percentage: SiO2: 38%–50%, CaO: 7%–10%, Na2O: 18%–25%, B2O3: 25%–35%.

3. The high-boron protective glaze according to claim 2, characterized in that, The mineral composition of the high-boron frit includes, by mass percentage: 36%–40% quartz, 30%–35% borax, 18%–25% soda ash, and 10%–13% calcite.

4. The high-boron protective glaze according to any one of claims 1 to 3, characterized in that, The chemical composition of the high boron protective glaze includes, by mass percentage: SiO2: 50%–60%, Al2O3: 8%–12%, Fe2O3: 0.1%–0.3%, TiO2: 0.03%–0.35%, CaO: 1%–8%, MgO: 1%–2%, K2O: 0.2%–0.5%, Na2O: 5%–9%, ​​ZnO: 1.5%–7%, B2O3: 6%–15%, and loss on ignition: 2.5%–4%.

5. A method for preparing building ceramics using high-boron protective glaze, characterized in that, Includes the following steps: Apply a surface glaze to the surface of the blank; Inkjet printing of decorative patterns on the surface of the blank after applying a glaze; Apply a high-boron protective glaze suitable for rapid firing in a roller kiln according to any one of claims 1 to 4 to the surface of the blank after inkjet printing of the decorative pattern; The green body after applying the high boron protective glaze is fired and polished to obtain architectural ceramics.

6. The preparation method according to claim 5, characterized in that, The high-boron protective glaze is applied by spraying, and the specific gravity of the glaze is controlled at 1.4–1.6 g / cm³. 3 The glaze application rate is 600–800 g / m². 2 .

7. The preparation method according to claim 5, characterized in that, The chemical composition of the glaze includes, by mass percentage: SiO2: 50%–60%, Al2O3: 20%–30%, Fe2O3: 0.1%–0.3%, TiO2: 0.01%–0.15%, CaO: 0.2%–1.6%, MgO: 0.1%–0.5%, K2O: 4%–5%, Na2O: 2%–3%, P2O5: 0.01%–0.1%, ZrO2: 4%–12%, and loss on ignition: 1%–3%.

8. The preparation method according to claim 5, characterized in that, The surface glaze is applied by spraying, and the specific gravity of the glaze is controlled at 1.35–1.6 g / cm³. 3 The glaze application rate is 500–800 g / m². 2 .

9. The preparation method according to claim 5, characterized in that, The firing temperature is 1170℃~1200℃, and the firing cycle is 30~40 minutes.

10. The preparation method according to claim 5, characterized in that, The gloss of the glaze of the architectural ceramics after firing before polishing is 70 to 99 degrees.